2019
DOI: 10.12928/telkomnika.v17i2.11791
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost communication system for explorer-class underwater remotely operated vehicle

Abstract: Disaster recovery from underwater earthquake, plane crashes into the sea, and monitoring underwater cables or piping for energy purpose are underwater missions for Remotely Operated Underwater Vehicle (ROV) in ASEAN MATE 2018 Competition. Two essentials factor to perform successfully in this ROV competition are design of an efficient communication protocol system and a low-cost communication hardware. In this research, an optimal communication system between RS-232 serial communication transmission and RS-485 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In [17,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101], the existing techniques for solving the high-cost issues in UIoT are discussed, and some methods are indicated herewith. In [89], Bridget Benson et al designed a low-cost acoustic modem to reduce underwater acoustic sensor network cost and power consumption.…”
Section: Low-cost Communication Methodsmentioning
confidence: 99%
“…In [17,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101], the existing techniques for solving the high-cost issues in UIoT are discussed, and some methods are indicated herewith. In [89], Bridget Benson et al designed a low-cost acoustic modem to reduce underwater acoustic sensor network cost and power consumption.…”
Section: Low-cost Communication Methodsmentioning
confidence: 99%
“…Autonomous underwater vehicle (AUV) considered one of the several studies that have discussed during the last decades due to its purposes and applications in different fields such as militaries, exploring the ocean submarines, oil and gas fields. In the literature, numerous controllers are presented for control the AUV the authors suggested different techniques to solve or handle the AUV problems like [1][2][3][4][5]. During the movement of AUV towards the vertical location, the sensors used in the AUV control model can add a considerable amount of noise which leads to change the tolerance and stability of the system as a result of that movement of AUV become unsettled.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, the development of underwater ROV starts from a navigation system based on a smartphone camera [3]. After that, the research continues with researching preferable wireless data communication for small underwater water ROV [4,5] and continues with tethered wired data communication [6]. Moreover, powerdistribution and consumption on ROV is one of the main research in previous research [7] The studies on maintaining depth is accomplished in several method based on the actuator, such as using thruster [8], using elevator [9] and using a bouyancy engine [10].…”
Section: Introductionmentioning
confidence: 99%